Osmotic perception of GABAergic synaptic transmission in the supraoptic nucleus of rats. (December 2020) - Ohbuchi, Toyoaki; Saito, Takeshi; Yokoyama, Toru; Hashimoto, Hirofumi; Maruyama, Takashi; Suzuki, Hideaki; Ueta, Yoichi
Abstract: Extracellular osmolality plays a crucial role in controlling the activation of neurons. Hypertonic stimulation modulates glutamatergic inputs to the supraoptic nucleus (SON) magnocellular neurosecretory cells (MNCs) putative vasopressin (VP) neurons through capsaicin-insensitive transient receptor potential vanilloid (TRPV) 1 channels on the presynaptic terminals. However, it remains unclear whether osmotic stimulation modulates GABAergic inputs to VP-secreting neurons within punched-out slices containing only the SON and the perinuclear zone. To answer this question, we studied the effects of various osmotic conditions on the miniature GABAergic postsynaptic currents (mGPSCs) using the whole-cell patch-clamp technique on rat SON putative VP-secreting neurons in small slice preparations. We revealed that incubation in hypertonic solution for 2 h reduced both the frequency and amplitude of the mGPSCs to the SON putative VP neurons, whereas the mGPSCs were unaffected when the external osmolality was changed from isotonic to hypotonic. Of interest, we found that changing from a hypertonic to hypotonic environment increased the frequency of the mGPSCs. This effect was independent of TRPV4. We hypothesize that two coordinated mechanisms may play an important role in the regulation of a wide range of physiological functions of VP.: 1) the modulation of GABAA receptor properties by brain-derived neurotrophic factor (BDNF)-induced tyrosine kinase B receptor-mediated signaling under hypertonic conditions, and 2) cell swelling-induced activation of whole-cell anion currents under hypotonic conditions.